(untitled) (Annals of Medical Research, 2023)
Aim: The aim of this study is to investigate the effectiveness of our treatment methods applied in the pain management of patients with HZ, PHN and risk factors associated with the development of HZ and PHN . Materials and Methods: The study was conducted in our hospital pain medicine clinic. The demographic data of the patients, in which phase of the disease they admitted, in which dermatomes the disease was occurred, what medical treatments they received and type of interventional treatments were applied between the dates of January 2019 and January 2023 were recorded. Also, pain reduction was evaluated as beneficial when there’s a reduction in the pain level equal or more than 50%, and below as useless. The dosage scheme and types of drugs used were recorded. The follow-up interval was determined as 6 weeks after the intervention. Results: While 131 (56.2 %) of 233 patients were diagnosed with HZ, 102 patients (43.8%) were diagnosed as PHN. The median age was significantly higher in the PHN group (p<0.001). Thoracic region (60.9%) is the most frequently involved dermatome for HZ and PHN, followed by lumbar, trigeminal nerve ophthalmic branch and cervical region. The most commonly used agents are pregabalin, tramadol and gabapentin, respectively. Interventional treatments, on the other hand, were generally effective regardless of the phase. Conclusion: It has been determined sympathetic blocks and epidural injections in acute and subacute periods are more effective, and peripheral nerve blocks are effective in both periods. While it was found to be effective the pulse radiofrequency in lumbar region, it was found to be effective in the chronic period while it was not effective in the facial dermatome in the acute period.